التدقيق الداخلي كآلية للحد من الفساد الإداري والمالي في المؤسسة الإقتصادية - تومي, ميلود; علون, محمد لمين (University of Eloued جامعة الوادي, 2016)
لقد أبرزت الإنهيارات والفضائح المالية ودعاوى الإحتيال المالي التي حدثت في السنوات الأخيرة ضعف أنظمة الرقابة الداخلية في العديد من المؤسسات مما زاد الإهتمام بالتدقيق الداخلي وأنظمة الرقابة الداخلية ودورهما في منظمات الأعمال الحديثة، وتعتبر وظيفة التدقيق الداخلي من الوظائف الهامة في المؤسسات لما لها من أثر في تصميم وتطوير نظام الرقابة الداخلية والإستخدام الأمثل للموارد المتاحة وكذلك المساهمة في تقييم وإدارة المخاطر، مما يعزز فرص الشركات من كشف ومواجهة ظاهرة الفساد المالي والإداري التي تعتبر أهم الأسباب الرئيسية لحدوث أزمات وإنهيارات كان لظهورها آثار مدوية ونتائج مدمرة مست معظم دول العالم وبالأخص الدول النامية، ومن خلال هذه المقال سنحاول تبيان أهمية إستخدام التدقيق الداخلي في المؤسسة الإقتصادية كآلية للحد من الفساد المالي والإداري The financial collapses and fraud issues which have occurred in recent years has demonstrated the weakness of internal control system in many institutions which increased the interest in internal audit and internal control system and their role in modern business establishment. The internal audit is considered as one of the most important functions which has an influence in designing and developing the internal control system and the optimal use of available resources. It also contributes to the assessment of risk management, and hence enhancing institution opportunities to encounter the phenomenon of financial and administrative corruption, which is the main important reason for the occurrence of crises. Through this article we will emphasize the importance of internal audit role in reducing financial and administrative corruption in economic institution
internal audit as a mechanism to reduce financial and managerial corruption economic institution
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: اد، الفساد المالي والإداري، التدقيق الداخلي، الرقابة الداخلية; Corruption, Financial and Administrative Corruption, Internal Audit, Internal Control